Case Study Risk Based Approach for Life Cycle Computerized System in Pharmaceutical Industry - Fitrio, Yodi (Journal of Applied Information, Communication and Technology, 2019)
Pharmaceutical industry is one of the industries that heavily regulated in most of country in the world. Regulation made by the regulatory is intended to ensure the system or process in the industry produce the product without impacting the safety, efficacy, integrity and quality of the product. Computerized system are commonly used by pharmaceutical manufacturing activities from planning, warehousing, production, engineering and testing in laboratories. Computerized system that used not only as information system or processing the data the system also used by the company to control their proses such automation system in production area. Recent report from regulatory showing there is increasing reports from regulatory regarding company failure in maintain their computerized system to comply with cGMP (current good manufacturing practice) from regulator.